Changing structure of the femoral neck across the adult female lifespan. - Poole, K; Mayhew, P; Rose, C; Brown, J; Bearcroft, P; Loveridge, N; Reeve, J (2010)
The anatomic distribution of cortical and cancellous bone in the femoral neck may be critical in determining resistance to fracture. We investigated the effects of aging on femoral neck bone in women. In this cross-sectional study, we used clinical multidetector computed tomography (MDCT) of the hips to investigate aging effects in 100 female volunteers aged 20 to 90 years. We developed a clinically efficient protocol to measure cortical thickness (C.Th) and cortical, trabecular, and integral bone mineral density (CtBMD, TrBMD, and iBMD in mg/cm(3)) in anatomic quadrants of the femoral neck. We used a nested ANOVA to evaluate their associations with height, weight, location in the femoral neck, and age of the subject. Age was the principal determinant of both cortical thickness and BMD. Age had significantly different effects within the anatomic quadrants; compared with young women, elderly subjects had relative preservation of the inferoanterior (IA) quadrant but strikingly reduced C.Th and BMD superiorly. A model including height, weight, and region of interest (and their interactions) explained 83% of the measurement variance (p < .0001). There were marked C.Th and BMD differences between age 25 and age 85 in the already thin superior quadrants. At 25 years the predicted C.Th of the superoposterior quadrant was 1.63 mm, whereas at 85 years it was 0.33 mm [-1.33 mm, 95% confidence interval (CI) of difference over 60 years -1.69 to -0.95]. By contrast, at 25 years mean C.Th of the IA quadrant was 3.9 mm, whereas at 85 years it was 3.3 mm (-0.6 mm, 95% CI -0.83 to -0.10). CtBMD of the IA region was equivalent at 25 and 85 years. In conclusion, elderly women had relative preservation of IA femoral neck bone over seven decades compared with young women but markedly lower C.Th and BMD in the other three quadrants. The IA quadrant transmits mechanical load from walking. Mechanical theory and laboratory tests on cadaveric femurs suggest that localized bone loss may increase the risk of fracture in elderly fallers. It remains to be determined whether this MDCT technique can provide better prediction of hip fracture than conventional clinical dual X-ray absorptiometry (DXA).